Rotational and translational alignment errors in 3D reconstruction of virus structures at high resolution. (6th October 2006) - Ji, Yongchang; Marinescu, Dan C.
The 3D reconstruction of virus structures at high resolution using CryoTEM data requires a very accurate rotational and translational alignment of individual views obtained experimentally. We discuss the geometrical foundations and the computational problems raised by rotational and translational alignment. We also outline the basic ideas for CTF correction.